Line Scan Diffusion Imaging of the Spine - Bammer, Roland; Herneth, Andreas M.; Maier, Stephan E.; Butts, Kim; Prokesch, Rupert W.; Do, Huy M.; Atlas, Scott W.; Moseley, Michael E. (American Journal of Neuroradiology, 2003)
BACKGROUND AND PURPOSE: Recent findings suggest that diffusion-weighted imaging might be an important adjunct to the diagnostic workup of disease processes in the spine, but physiological motion and the challenging magnetic environment make it difficult to perform reliable quantitative diffusion measurements. Multi-section line scan diffusion imaging of the spine was implemented and evaluated to provide quantitative diffusion measurements of vertebral bodies and intervertebral disks.METHODS: Line scan diffusion imaging of 12 healthy study participants and three patients with benign vertebral compression fractures was performed to assess the potential of line scan diffusion imaging of the spinal column. In a subgroup of six participants, multiple b-value (5–3005 s/mm2) images were obtained to test for multi-exponential signal decay.RESULTS: All images were diagnostic and of high quality. Mean diffusion values were (230 ± 83) × 10−6 mm2/s in the vertebral bodies, (1645 ± 213) × 10−6 mm2/s in the nuclei pulposi, (837 ± 318) × 10−6 mm2/s in the annuli fibrosi and ranged from 1019 × 10−6 mm2/s to 1972 × 10−6 mm2/s in benign compression fractures. The mean relative intra-participant variation of mean diffusivity among different vertebral segments (T10-L5) was 2.97%, whereas the relative difference in mean diffusivity among participants was 7.41% (P < .0001). The estimated measurement precision was <2%. A bi-exponential diffusion attenuation was found only in vertebral bodies.CONCLUSION: Line scan diffusion imaging is a robust and reliable method for imaging the spinal column. It does not suffer as strongly from susceptibility artifacts as does echo-planar imaging and is less susceptible to patient motion than are other multi-shot techniques. The different contributions from the water and fat fractions need to be considered in diffusion-weighted imaging of the vertebral bodies.